Sign Language Interpreters Encounter Challenges in Inclusive Settings at Public and Private Institutions - Fozia Waqar, Syeda Seerat Hassan, (JIE, 2024)
The hearing-impaired child's native language is signing language. The relevance of the sign language interpreter has expanded in educational settings, particularly in inclusive settings, and they serve as a link between the normal and hearing-impaired communities. This research was conducted in Lahore. Sign Language Interpreters Face Challenges in Inclusive Settings in Public and Private Institutions was the topic of the phenomenon. T